2001
DOI: 10.1002/1521-3951(200107)226:1<69::aid-pssb69>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Density Functional Theory Calculations of Photoabsorption of Fluorinated Cyclic Molecules in the Vacuum Ultraviolet Region

Abstract: Subject classification: 71.15.Mb; 78.40.Me; S12Time-dependent density functional theory (TD-DFT) calculations of the photoabsorption of molecules in the vacuum ultraviolet region have been performed in order to aid in the design of transparent materials for use as photoresists for F 2 lithography (157 nm). The method including an empirical equation for correcting the calculated transition energy is described. We have used the TD-DFT approach to predict the photoabsorption of substituted benzenes, and cycloalka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…We are particularly interested in exploiting time-dependent DFT (TD-DFT) to predict the UV−visible spectra of a wide range of molecules from new photolithographic polymers for the production of semiconductors to biomolecules for neurotoxins . Such TD-DFT calculations have a strong dependence on the orbital energies.…”
Section: Introductionmentioning
confidence: 99%
“…We are particularly interested in exploiting time-dependent DFT (TD-DFT) to predict the UV−visible spectra of a wide range of molecules from new photolithographic polymers for the production of semiconductors to biomolecules for neurotoxins . Such TD-DFT calculations have a strong dependence on the orbital energies.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the case of ground states, time-dependent density functional theory (TD-DFT) for treating excited-state properties has only recently been applied to molecules, , although the theory itself was first proposed more than 20 years ago. Recent work has shown that TD-DFT can be used to reliably predict not only the location of the UV−vis excitation but also the oscillator strength (intensity of the transition). , In addition, Adamo and Barone have tested TD-DFT calculations in models of aqueous solutions, although the calculated results indicate that the solvent shifts of the calculated excitation energies are small compared to the accuracy required to qualitatively predict the color of a compound.
1
…”
Section: Introductionmentioning
confidence: 99%
“…Further theoretical calculations are required to determine the validity of this assumption. 12,21 An important result of our investigation is recognizing the essential wavelength independence of the photolysis of the model compounds. This result establishes the possibility that exploratory experiments of the photochemistry of materials which absorb strongly in the deep UV may be examined with the much more convenient equipment that is available in the near UV.…”
Section: Resultsmentioning
confidence: 98%